Physicochemical and bioactive constituents, microbial counts, and color components of spray-dried Syzygium cumini L. pulp powder stored in different packaging materials under two controlled environmental conditions - Kumar, Vishal; Singh, Chandra Shekhar; Bakshi, Shiva; Kumar, Sudhir; Yadav, Satya Prakash; Al-Zamani, Zakarya Ali Saleh; Kumar, Pankaj; Singh, Upendra; Meena, Kamlesh Kumar; Bunkar, Durga Shankar; Paswan, Vinod Kumar (Frontiers in Nutrition, 2023)
In recent times, the demand for functional food items imparting health benefits is rising day by day. Blueberry (Syzygium cumini L.) fruit has high anthocyanin content and other functional attributes. However, this seasonal fruit is highly perishable and a large proportion of it goes unharvested and wasted worldwide. Spray drying of the fruit pulp can impart improved shelf life ensuring long duration availability to consumers for exploiting its health benefits. The keeping quality varies according to the type of packaging material and the storage environment. Therefore, in this study the shelf life-span of the spray-dried Syzygium cumini L. pulp powder (SSCPP) was investigated during six months of storage under three types of packaging materials (polystyrene, metalized polyester and 4-ply laminates) at low temperature environment (LTE) and at ambient environment conditions. Physico-chemical and stability of bioactive principles (TPC and TAC), microbial counts and colour components were analyzed at 0, 2, 4 and 6 months of storage. There was a significant gradual loss of dispersibility and solubility with increase in flowability, bulk density and wettability during the entire storage period under all three packaging materials. The TSS, pH, TPC, TAC and also the microbial counts decreased in the SSCPP both at ambient and at LTE conditions while the study. Among all packaging materials, 2 This is a provisional file, not the final typeset article the 4-ply laminate was found to be the most appropriate and safe for storage of spray dried SCPP at LTE conditions.